Training report on food safety risk assessment and management - Sinh Dang-Xuan; Unger, Fred (International Livestock Research Institute, 2024)
The Agroecology and Safe Food System Transitions (ASSET) project is a five-year regional initiative (2020–2025) funded by AFD, the EU, and FFEM, implemented in Cambodia, Laos, Myanmar, and Vietnam. The project aims to promote agroecology for sustainable food and agricultural systems through capacity building, technical and organizational innovations, and policy dialogue.